Pheromone races of Cydia splendana (Lepidoptera, Tortricidae) overlap in host plant association and geographic distribution - Bengtsson, Marie; Boutitie, Anne; Jósvai, Julia; Toth, Miklos; Andreadis, Stefanos; Rauscher, Stefan; Unelius, C. Rikard; Witzgall, Peter (Frontiers in Ecology and Evolution, 2014)
Identification of the sex pheromone of Cydia splendana (Lepidoptera, Tortricidae) by pheromone gland analysis followed by field trapping with synthetic compounds shows the occurrence of two pheromone races. Acorn moth females from Sweden, where oak Quercus robur is the only host plant, use a blend of the E,Z and E,E isomers of 8,10-dodecadien-1-yl acetate. In Central and Southern Europe, where C. splendana feeds on chestnut Castanea sativa and several species of oak, males respond to another isomer blend, E,E and Z,E. The distribution of the two pheromone races of C. splendana overlaps in Northern France, where they share oak as plant host. Differences in sex communication signals lead to behavioural pre-mating isolation between these populations, and emphasize the role of specific mate recognition in speciation events.